The Lived Experiences of African American Centenarians: Narrative Exploration From a Life Course Theory Perspective. (19th April 2021) - Heinz, Melinda; Bishop, Alexander J; Finchum, Tanya
Abstract: Background and Objectives: The purpose of this study was to examine examples of inequality experienced by African American centenarians throughout the life course. Research Design and Methods: Data were derived from 111 oral history transcripts from the Oklahoma Oral History Project. A subsample of all centenarians who identified as African American ( n = 12) was utilized. An interpretive phenomenological approach and thematic analysis were used to review and code each narrative. Results: Findings revealed 2 themes: (a) historical time and place with subthemes on family lineage, segregation, discrimination, and racism, and societal changes; (b) resource buffers against inequality with subthemes on multigenerational transmission, support and cultural connectedness, religion and spirituality, and self-reliance. Several centenarians acknowledged having grandparents who were slaves and others reported hidden family lineage due to complicated mixed-race dynamics. Work histories were affected by the historical era, with limited "domestic" positions for women. Experiences with education varied, with one centenarian commenting on his legacy of teaching at historically Black schools whereas others expressed difficulty in keeping up with school and regret for not finishing. Discussion and Implications: This is one of the first studies to explore life course experiences specific to African American centenarians. Centenarians in this study possessed survival skills and various support systems including community and religious/spiritual support, perhaps buffering against the impact of cumulative racial inequality.